Try NerdPal! Our new app on iOS and Android

# Expand the expression $\left(x+5\right)^2$

## Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$x^2+10x+25$
Got another answer? Verify it here

## Step-by-step Solution

Problem to solve:

$\left(x+5\right)^2$
1

A binomial squared (sum) is equal to the square of the first term, plus the double product of the first by the second, plus the square of the second term. In other words: $(a+b)^2=a^2+2ab+b^2$

• Square of the first term: $\left(x\right)^2 = x^2$
• Double product of the first by the second: $2\left(x\right)\left(5\right) = 2\cdot 5x$
• Square of the second term: $\left(5\right)^2 = 5^2$

$x^2+2\cdot 5x+5^2$

Learn how to solve special products problems step by step online.

$x^2+2\cdot 5x+5^2$

Learn how to solve special products problems step by step online. Expand the expression (x+5)^2. A binomial squared (sum) is equal to the square of the first term, plus the double product of the first by the second, plus the square of the second term. In other words: (a+b)^2=a^2+2ab+b^2<ul><li>Square of the first term: \left(x\right)^2 = x^2</li><li>Double product of the first by the second: 2\left(x\right)\left(5\right) = 2\cdot 5x</li><li>Square of the second term: \left(5\right)^2 = 5^2</li></ul>. Multiply 2 times 5. Calculate the power 5^2.

$x^2+10x+25$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$\left(x+5\right)^2$